2004
DOI: 10.1007/s11182-005-0032-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure, unelastic properties, and deformation behavior of ultrafine-grained titanium

Abstract: The results of investigations into the structure, unelastic properties, deformation behavior, strength, and plasticity of ultrafine-grained titanium produced by equichannel angular pressing are discussed. Particlular emphasis has been placed on the grain-boundary unelasticity and the effects of external thermal and thermal-force actions on the deformation behavior and plastic deformation localization at the meso-and macroscale levels. The influence of cold plastic deformation of ultrafine-grained titanium on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The plastic strain localization pattern in metals and alloys changes radically when a nanostructural state forms. Investigations on the deformation surface relief of tensile specimens at room temperature [7][8][9][10][11][12] have shown that plastic strain localization is evident in nanostructured metals and alloys as meso-and macrobands 1-10 and 300-500 µm in width, respectively (Fig. 1).…”
Section: Plastic Strain Localization In Nanostructured Metallic Mater...mentioning
confidence: 99%
See 1 more Smart Citation
“…The plastic strain localization pattern in metals and alloys changes radically when a nanostructural state forms. Investigations on the deformation surface relief of tensile specimens at room temperature [7][8][9][10][11][12] have shown that plastic strain localization is evident in nanostructured metals and alloys as meso-and macrobands 1-10 and 300-500 µm in width, respectively (Fig. 1).…”
Section: Plastic Strain Localization In Nanostructured Metallic Mater...mentioning
confidence: 99%
“…In [8,9], nanostructured titanium was used as an example to study the correlation between plastic strain localization and deformation stages in tensile stress-strain curves. The strain-hardening stage in the engineering stress-strain curve was found to correspond to the nucleation and development of mesoscopic localized plastic deformation bands.…”
Section: Plastic Strain Localization In Nanostructured Metallic Mater...mentioning
confidence: 99%